The Roles of Volunteers in Community Development in Kampung Baca Bukik Ase - Gita Noviyanti Sadli; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
The achievement of community development goals in Kampung Baca Bukik Ase is caused by the existence of volunteers in every implementation of development activities. This study aims to describe the roles of volunteers in terms of educating the community (educating), facilitating community development activities (facilitative), building relationships with various sources for the continuation of community development activities (representative), and managing various matters relating to community development activities (technical). This type of research is qualitative research using a case study approach. Data sources in this study consisted of research subjects, namely permanent volunteers in Kampung Baca Bukik Ase, and research informants, namely managers and volunteers from Kampung Baca Bukik Ase partners. Data collection techniques used in this study are interviews and documentation with data analysis used, namely data reduction, data presentation, and drawing conclusions, as well as data validity techniques of the results of this study were conducted by triangulation of sources. The results of this study indicate that role of volunteers in community development in Kampung Baca Bukik Ase are: (1) volunteers have performed their roles properly and appropriately in raising awareness and providing useful information for the community, as well as assistance provided by volunteers in organizing activities in accordance with community needs; (2) volunteers have carried out appropriate social development to solve problems in carrying out community development activities, are involved in solving problems faced by the community and recognize and utilize community resources and skills; (3) volunteers have created a relationship and developed networks and established partnerships with partners and shared information about activities through social media; (4) volunteers have nor been involved in the management of activities and finance, but have used modern technology in every development activity carried out.Keywords: Roles, Volunteers, Community Development